The R2R3-type MYB gene OsMYB91 has a function in coordinating plant growth and salt stress tolerance in rice. (July 2015) - Zhu, Ning; Cheng, Saifeng; Liu, Xiaoyun; Du, Hao; Dai, Mingqiu; Zhou, Dao-Xiu; Yang, Wenjing; Zhao, Yu
Highlights: Expression of OsMYB91 can be greatly induced by salt stress. Salt stress leads to DNA demethylation and changes of histone modifications in OsMYB91 gene locus. Over-expression of OsMYB91 plants enhances tolerance to salt stress and reduce plant growth. Over-expression OsMYB91 plants increase proline levels and capacity to scavenge active oxygen under salt stress. OsMYB91 coordinates rice tolerance to abiotic stress and plant growth by regulating SLR1 expression. Abstract: Plants have evolved a number of different mechanisms to respond and to adapt to abiotic stress for their survival. However, the regulatory mechanisms involved in coordinating abiotic stress tolerance and plant growth are not fully understood. Here, the function of OsMYB91, an R2R3-type MYB transcription factor of rice was explored. OsMYB91 was induced by abiotic stress, especially by salt stress. Analysis of chromatin structure of the gene revealed that salt stress led to rapid removal of DNA methylation from the promoter region and rapid changes of histone modifications in the locus. Plants over-expressing OsMYB91 showed reduced plant growth and accumulation of endogenous ABA under control conditions. Under salt stress, the over-expression plants showed enhanced tolerance with significant increases of proline levels and a highly enhanced capacity to scavenge active oxygen as well as the increased induction of OsP5CS1 and LOC_Os03g44130 compared to wild type, while RNAi plants were less sensitive. In addition, expression of OsMYB91 was also induced by other abiotic stresses and hormone treatment. More interestingly, SLR1, the rice homolog of Arabidopsis DELLA genes that have been shown to integrate endogenous developmental signals with adverse environmental conditions, was highly induced by OsMYB91 over-expression, while the salt-induction of SLR1 expression was impaired in the RNAi plants. These results suggested that OsMYB91 was a stress-responsive gene that might be involved in coordinating rice tolerance to abiotic stress and plant growth by regulating SLR1 expression.